Stres pada Pasien Hipertensi - Ni Made Wedri; VM Endang SP Rahayu (Jurnal Gema Keperawatan, 2017)
The aim is to know the description of stress level of hypertension patient at Tabanan III Public Health Center 2017. The sampling technique used is non probability sampling ie purposive sampling, with the number ofcrespondents is 59 people. Data collection tool used is DASS 42 (Depression Anxiety Stress Scale) 42 a number of 14 statements. The results showed that most respondents were 22 people (37.3%) aged 65 years. The highest percentage by sex was 27 women (54.2%). Most respondents did not work 17 people (28.8%). Based on the classification of hypertension most of the respondents 32 people (54.2%) moderate to very severe hypertension. The picture of stress level that is 29 people (49,2%) have medium to very heavy stress, 20 people (33,9%) light stress and only 10 people (16,9%) normal.